Dynamic control of current and voltage waveforms and droplet transfer for ultrasonic-wave-assisted underwater wet welding. (5th November 2019) - Wang, Jianfeng; Sun, Qingjie; Hou, Shaojun; Zhang, Tao; Jin, Peng; Feng, Jicai
Abstract: Ultrasonic vibration can change the dynamic behavior of the bubble and improve the process stability in underwater wet welding (UWW); thus, it has been attempted to profitably control metal transfer process. Arc signals about welding current and arc voltage together with the high-speed imaging detected in conventional UWW and ultrasonic-wave-assisted UWW (U-UWW) were used as information source for determining the droplet transfer mode. The results show that the change in the characteristics of bubble motion affects the droplet transfer process in U-UWW. During the short-circuiting transfer process in small arc voltage, the frequency of arc extinction and the peak of short-circuiting current are both decreased. During the droplet repelled transfer process in middle arc voltage, the droplet repulsive phenomenon is weakened, and the transfer frequency is increased from 7.9 Hz to 10.5 Hz at 34 V. Meanwhile, the droplet diameter is reduced and its transfer stability is improved. During the droplet repelled transfer process in high arc voltage, the frequency and duration time of arc extinction are both reduced. The underlying difference of droplet transfer process between conventional UWW and U-UWW was investigated by the two aspects including ultrasonic wave effect and dynamic bubble effect. Graphical abstract: Unlabelled Image Highlights: Droplet transfer behavior under an acoustic field was assessed by visual sensing method. Ultrasonic-wave-assisted underwater wet welding proved to be effective in regulating the control of the bubble. Ultrasonic wave caused variations in droplet transfer, related to the variation of bubble behavior. Ultrasonic wave could minimize the potential for gas flow drag force and buoyant force generated by the bubble.